2009
DOI: 10.3324/haematol.13619
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of inherited microcytic anemia due to defects in iron acquisition or heme synthesis

Abstract: © F e r r a t a S t o r t i F o u n d a t i o nAIn this paper we will review the new information available on the iron acquisition pathway by developing erythrocytes and its regulation, and we will consider only inherited microcytosis due to heme synthesis or to iron metabolism defects. Iron and erythropoiesis Iron acquisition pathway in erythroid cellsDeveloping erythroid cells in the bone marrow acquire iron from the plasma iron-transferrin (Tf) complex, through the transferrin receptor (TfR) mediated pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
0
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(106 citation statements)
references
References 124 publications
(130 reference statements)
3
92
0
11
Order By: Relevance
“…It has been suggested that the EPO-triggered therapeutic improvement of iron-deficiency anemia could be due to the anti-apoptotic effect of EPO. 7,32 The present study confirms this hypothesis. Colony-forming assays showed significantly improved in vitro growth of our patient's DMT1-mutant post-treatment BFU-E progenitors compared to pre-treatment BFU-E pro- genitors.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It has been suggested that the EPO-triggered therapeutic improvement of iron-deficiency anemia could be due to the anti-apoptotic effect of EPO. 7,32 The present study confirms this hypothesis. Colony-forming assays showed significantly improved in vitro growth of our patient's DMT1-mutant post-treatment BFU-E progenitors compared to pre-treatment BFU-E pro- genitors.…”
Section: Discussionsupporting
confidence: 82%
“…19 The possible involvement of any substantial increase in iron utilization by individual erythroid cells as a contributing factor to the positive effects of EPO therapy can be ruled out by the fact that the patients' erythrocyte characteristics (MCV and MCH) remained unchanged with EPO supplementation. 7,32 Our observation of decreased MCV and MCH in the mk/mk mice following EPO treatment further supports this conclusion.…”
Section: Discussionsupporting
confidence: 76%
“…In the remaining forms of porphyria, erythrocyte non-heme protoporphyrins generally lie within the reference range [13]. Lead and other heavy metal intoxication [15][16][17] and a variety of sideroblastic [18] and inherited microcytic anemias [19] may also be responsible for alterations in erythrocyte PPIX and ZnPP. A recent study found decreased PPIX fluorescence in erythrocytes from diabetic compared to non-diabetic mice, suggesting the possible use of PPIX as a diagnostic marker for monitoring of diabetes [20].…”
Section: Introductionmentioning
confidence: 99%
“…The mouse also represents a unique model to identify novel players in iron homeostasis [7,8,9]. Finally, it has been shown that the occurrence, in mice, of genetic mutations responsible for human iron disorders, for example hemochromatosis and anemia, fully recapitulate the human diseases, thus stressing the importance of mouse models for studying the pathogenetic mechanisms of these diseases and for testing new therapies [10,11].…”
Section: Introductionmentioning
confidence: 99%